Peran Diagnostik Stiff Rim Sign pada Shear Wave Elastography untuk rekomendasi dalam menuntun biopsi pada lesi payudara BI-RADS 3 dan 4 - Fauziyyah Nuur Al Azizah; Astien Astien; Meita Ranika; Agnes Wanda Suwanto; Tantri Dwi Kaniya Retno Hapsari; Januar Ishak Hutasoit; Santa Mercylia (Fakultas Kedokteran Universitas Trisakti, 2026)
Breast cancer remains the most frequently diagnosed malignancy among women worldwide and continues to represent a major public health challenge. Accurate characterization of breast lesions is essential for early diagnosis and appropriate clinical management. Conventional ultrasound is widely used to evaluate breast lesions and classify them using the Breast Imaging Reporting and Data System (BI-RADS). However, differentiating benign from malignant lesions remains difficult, particularly in BI-RADS categories 3 and 4, which often lead to diagnostic uncertainty and unnecessary biopsies. Shear wave elastography (SWE) has emerged as an adjunct imaging technique that evaluates tissue stiffness and provides additional diagnostic information beyond conventional ultrasound. One characteristic elastography feature is the stiff rim sign, which appears as increased peri-lesional stiffness surrounding a breast mass and may reflect malignant tumor infiltration and stromal reaction. This systematic review aimed to evaluate the diagnostic role of the stiff rim sign detected by shear-wave elastography in differentiating benign from malignant breast lesions and its potential utility in guiding biopsy recommendations for BI-RADS category 3 and 4 lesions. A comprehensive literature search was conducted in PubMed, the Cochrane Library, and ScienceDirect to identify relevant studies assessing SWE and peri-lesional stiffness features in breast lesions. Studies that met predefined inclusion criteria were screened and evaluated, and relevant data on diagnostic performance were extracted for qualitative synthesis. The literature search identified 71 records, of which six studies met the eligibility criteria and were included in the final analysis. Across the included studies, the stiff rim sign demonstrated moderate to high diagnostic performance in differentiating malignant from benign breast lesions. Several studies reported high sensitivity, specificity, and area under the receiver operating characteristic curve when elastography findings were combined with conventional ultrasound parameters. Overall, the stiff rim sign detected by shear wave elastography appears to be a valuable imaging feature that may improve diagnostic accuracy and assist clinicians in guiding biopsy decisions for patients with BI-RADS 3 and 4 breast lesions.